災害時の栄養・食生活支援に対する自治体の準備状況等に関する全国調査 - Ito Seira; Sudo Noriko; 笠岡（坪山） 宜代; 山田 佳奈実; 山村 浩二; Yamashita Masayo; 山本 眞由美; Shimoura Yoshiyuki; 小松 龍史 (Journal of the Japan Dietetic Association, 2015)
A questionnaire was sent to all local governments in Japan; 47 prefectures, 20 designated cities, 42 core cities, 8 ordinance-designated cities, 23 special wards, and 1649 municipalities. We asked about their preparedness for nutrition assistance, dispatch of administrative dietitians (ADs) to the affected areas of the Great East Japan Earthquake, and what kind of support municipalities want from ADs in prefectural health centers. The return rate was 71.1% (n=1272). The percentage of autonomies that dispatched ADs was significantly higher in those with past experience of large earthquakes. About 70% of autonomies required more information to promote the preparation of nutrition assistance in emergencies. Expected roles of ADs in prefectural health centers in normal times were to provide training and manuals or guidelines for municipalities, especially for those without ADs. During disaster times, ADs in prefectural health centers were expected to help municipalities within the jurisdiction to provide support activities for the residents affected by the disaster, contacting relevant organizations or other support groups. The system should be improved in order for ADs to engage in support activities soon after a disaster has occurred, with the full cooperation of other staff. 全国自治体による東日本大震災被災地への行政栄養士派遣の実態と、東日本大震災2 年半後における災害時の栄養・食生活支援のための職員の準備状況および市町村が保健所に期待する支援内容を探ることを目的とした。全国の都道府県、政令指定都市、中核市、保健所政令市、特別区の衛生主管部（局）長、市町村の保健医療福祉担当者を対象とした質問紙調査を実施した（回収率71.1％：N＝1,272）。東日本大震災被災地へ行政栄養士を派遣した割合は、それ以前に被災経験のある自治体において有意に高かった。行政栄養士を配置していない市町村では、栄養・食生活支援に関する研修や指導を受けたことのある割合が10.2％（n＝17）と低く、保健所による積極的な支援が必要である。災害時において、保健所は災害対策本部や支援団体等との連絡・調整を行い、市町村をサポートすることが期待される。行政栄養士が災害発生直後から、他職種の理解のもと、栄養・食生活支援に携わるための体制を整備していくことが求められる。